Coronary and cardiovascular risk estimation for primary prevention:validation of a new Sheffield table in the 1995 Scottish health survey population. Issue 7236 (11th March 2000) - Wallis, Erica J; Ramsay, Lawrence E; Haq, Iftikhar UI; Ghahramani, Parviz; Jackson, Peter R; Yeo, Karen Rowland; Yeo, Wilfred W
Abstract: Objective: To examine the accuracy of a new version of the Sheffield table designed to aid decisions on lipids screening and detect thresholds for risk of coronary heart disease needed to implement current guidelines for primary prevention of cardiovascular disease. Design: Comparison of decisions made on the basis of the table with absolute risk of coronary heart disease or cardiovascular disease calculated by the Framingham risk function. The decisions related to statin treatment when coronary risk is ≥years; aspirin treatment when the risk is ≥ 15% over 10 years; and the treatment of mild hypertension when the cardiovascular risk is≥0% over 10 years. Setting: The table is designed for use in general practice. Subjects: Random sample of 1000 people aged 35–64 years from the 1995 Scottish health survey. Main outcome measures: Sensitivity, specificity, and positive and negative predictive values of the table. Results: 13% of people had a coronary risk of ≥15%, and 2.2% a risk of ≥30%, over 10 years. 22% had mild hypertension (systolic blood pressure 140–159 mm Hg). The table indicated lipids screening for everyone with a coronary risk of ≥15% over 10 years, for 95% of people with a ratio of total cholesterol to high density lipoprotein cholesterol of ≥8.0, but for <50% with a coronary risk of <5% over 10 years. Sensitivity and specificity were 97% and 95% respectively for a coronary risk of ≥15% over 10 years; 82% and 99% for a coronary risk of ≥30% over 10 years; and 88% and 90% for a cardiovascular risk of ≥20% over 10 years in mild hypertension. Conclusion: The table identifies all high risk people for lipids screening, reduces screening of low risk people by more than half, and ensures that treatments are prescribed appropriately to those at high risk, while avoiding inappropriate treatment of people at low risk.